KERJASAMA GURU BK DENGAN PERSONEL SEKOLAH DALAM MELAKSANAKAN KEGIATAN LAYANAN BK DI SEKOLAH MENENGAH ATAS NEGERI (SMAN) 4 KERINCI - Satya Anggi Permana (Menara Ilmu, 2018)
SMAN 4 Kerinci (Senior High School) is one of favorite schools which has potentialto conduct guidance and counseling service optimally. This is supported by its conducivecondition and the sufficient number of the teachers. All of the teachers have qualification inGuidance of Counseling education. In addition, this school has adequate facilities.Unfortunately, the phenomena in the field indicated that the guidance and counseling servicewas not effectively conducted. This research was intended to describe the implementation ofGuidance and Counseling service in that school. This was a qualitative research whichapplied phenomology approach. The informants of the research were the school fellowsincluding headmaster, vice headmaster, guidance and counseling teachers, subject teachersand classroom teachers. The data where collected through observation, interview anddocumentation study. To check the trustwortiness of the data, there were four conducted (1)credibility, (2) transferability, (3) depedability, and (4) conformability. The data gatheredwhere analyzed by (1) data reduction, (2) displaying the data and, (3) drawingconclusion/verifying. The research findings showed that the Guidance and Counseling servicewas not yet conducted optimally at SMAN 4 Kerinci. The cooperation between Guidance andCounseling Teachers with other school fellows was not yet established. This researchconcluded that the conducive atmosphere, the availability of sufficient qualified teachers, theadequate number of school fellows and the availability of sufficient facilities unless they weresupported by good cooperation among related parties, the Guidance and Counseling servicewould not be optimally accomplished. Based on these conclusions, it was suggested: (1) theGuidance and Counseling teachers to be professional in carrying out their duties andresponsibility and to be albe to cooperate with other school fellows. and (2) the school fellowsto understand their roles in implementing Guidance and Counseling activities at school and bealbe to get involved actively in.Key Terms: Guidance and Counseling, Cooperation